Delay discounting in mild cognitive impairment - Coelho, Sara (2016)
Introduction : Patients with mild cognitive impairme nt (MCI) may make suboptimal decisions particularly in complex situations, and thi s could be due to temporal discounting, the tendency to prefer immediate rewards over delayed but larger rewards. The present study proposes to evaluate intertemporal prefere nces in MCI patients as compared to healthy controls. Method : Fifty-five patients with MCI and 57 h ealthy controls underwent neuropsy- chological evaluation and a delay discounting questionnaire, which evaluates three para- meters: hyperbolic discounting ( k ), the percentage of choices for delayed and later rewards (%LL), and response consistency (Acc). Results : No significant differences were found in the delay discounting questionnaire between MC I patients and controls for the three reward sizes considered, small, medium, and large, using both k and %LL parameters. There were also no differences in the response consistency, Acc, between the two groups. Conclusions : Patients with MCI perform similarly to healthy controls in a delay discounting task. Memory deficits do not notably affect intertemporal preferences.